Conceptualization Value- Based Management of Islamic Educational Facilities and Infrastructure: Integration of POAC Functions and the Amanah Principle - Yan Sopyanurdin Sopyanurdin (UIN Siber Syekh Nurjati Cirebon, 2026)
Abstract :This article conceptualizes values-based management of facilities and infrastructure in Islamic education by integrating modern management functions with Islamic ethical principles. The study addresses the gap in existing research, which predominantly treats facilities management as a technical-administrative process and gives limited attention to Islamic values as operational management principles. The objective of this study is to formulate a conceptual framework for managing educational facilities and infrastructure in Islamic institutions based on value integration. A qualitative library research approach was employed, drawing on academic books, educational regulations, and peer-reviewed journal articles related to educational management and Islamic education. Data were analyzed through data reduction, thematic categorization, and conceptual synthesis. The findings indicate that the management functions of planning, organizing, actuating, and controlling can be strengthened when grounded in the principles of trustworthiness ( mandate ), efficiency, responsibility, and accountability. Facilities and infrastructure are thus positioned not only as physical learning supports but also as institutional trusts that require ethical and professional governance. The study concludes that integrating Islamic values into each management function provides a more holistic and meaningful framework for managing educational facilities in Islamic education institutions and offers a conceptual reference for future empirical development.Keywords : Values-based Management; Educational Facilities and Infrastructure; Islamic Education.